Aversion and othering: the discourse of food disgust and subalternity in Indian cinema - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2024)
Food plays a significant role in the cultural integration and rejection of identities. It is because the notion of food and its associated signifiers contribute to the very structural framing of public discourses in relation to the power dynamics that define social status. Food choices and eating are related to socio-cultural contexts, environment, economy, and political power (McMichael). The symbolism of food in arts and literature has been so profound in many forms and they are often used to contextualise the violence, discrimination, inequality, racial prejudices, and excommunication of certain categories of people and their histories of resistance, cultural communications, and social inclusion (Ojwang 68). Food can be viewed as a unique and powerful "semiotic device" that provides meaning to those who consume them (Appadurai 494). The cultural and political character of food shapes the public identity of a class in a hierarchical social order. Food studies are often integrated with cultural studies to examine how food as a metanarrative gives information about individual subjects and their positions in the world around us (Ashley, Hollows, Jones, and Taylor).
Keywords: Indian cinema; food; cultural integration; semiotic device; social status